2021
DOI: 10.1097/gox.0000000000003296
|View full text |Cite
|
Sign up to set email alerts
|

Safety of Copolyamide Filler Injection for Breast Augmentation

Abstract: Background: Although injections with copolyamide fillers (Aquafilling/Los Deline and Aqualift/Activegel) are currently used widely for breast augmentation, many complications have been reported. A recent position statement by a Korean aesthetic/reconstructive breast surgery society indicated these fillers are the same as polyacrylamide gel (PAAG), which is widely prohibited due to complications. To test this statement, this retrospective cohort study examined the clinical complications after breast … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
36
1
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(39 citation statements)
references
References 34 publications
0
36
1
2
Order By: Relevance
“…There might exist minimal differences in the polymer structure of the Aquafilling® gel and PAAG filler, but the overall composition of polyacrylamide in both gel types appears to be quite similar. Hence, features of PAAG fillers as well as the known complications after injection as body fillers are expected to be similar for the use of Aquafill-ing® [4,7,9,17,26].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…There might exist minimal differences in the polymer structure of the Aquafilling® gel and PAAG filler, but the overall composition of polyacrylamide in both gel types appears to be quite similar. Hence, features of PAAG fillers as well as the known complications after injection as body fillers are expected to be similar for the use of Aquafill-ing® [4,7,9,17,26].…”
Section: Discussionmentioning
confidence: 99%
“…Even though the manufacturer of Aquafilling®, recently renamed Los Deline® (Biomedica, Prague, Czech Republic), initially claimed that the gel had features differentiating it from PAAG, the overall composition of polyacrylamide in both gel types seems to be quite similar, and the complications after injection of PAAG and Aquafilling® for breast augmentation are thought to be equivalent [1,4,9,17] On these accounts, possible breastfeeding problems subsequent to filler injection for augmentation in young women should not be disregarded. Patients might present with markedly enlarged and painful breasts, and distinction between galactocele formation and inflammatory processes based on physical examination and ultrasound findings can be challenging.…”
Section: Introductionmentioning
confidence: 99%
“…This similarity was furthermore confirmed by the study “Safety of Copolyamide Filler Injection for Breast Augmentation” by Nomoto et al, showing that these substances share the same chemical composition and complication profile. 14 Our approach was dictated by the severity of the symptoms, and the mentioned aesthetic compromises accepted by the patients. We are aware that our approach cannot be generalized due to the small number of patients.…”
Section: Discussionmentioning
confidence: 99%
“…The average duration from injection to developing the complication was 6.1 years [97]. Nomoto et al reported that 29 patients who received copolymer-filler injection presented with concerns (deformity, gel migration, infection, induration, pain, and fistula) [98]. The mean duration between injection and consultation was 1.8 years.…”
Section: Hydrophilic Gel Fillersmentioning
confidence: 99%